2009
DOI: 10.1021/ja905143m
|View full text |Cite
|
Sign up to set email alerts
|

Direct Asymmetric Reductive Amination

Abstract: Asymmetric reductive amination of beta-keto amides catalyzed by the chiral catalyst Ru(OAc)(2)((R)-dm-segphos) produces unprotected beta-amino amides with high yields and high enantioselectivities (94.7-99.5% ee). This "one-pot" methodology is general in substrate scope and has been successfully employed to produce sitagliptin with 99.5% ee and 91% assay yield. The excellent reaction efficiency is attributed to the remarkable tolerance to high concentrations of ammonium ion, the high chemoselectivity, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(77 citation statements)
references
References 14 publications
2
69
0
6
Order By: Relevance
“…c o m / l o c a t e / t e t a s y Rh-catalyzed asymmetric hydrogenations of an enamine under high pressure; 11 (iii) biocatalytic or Ru-catalyzed reductive aminations of a b-ketoamide. 12 Quite recently, Davies et al 13 reported on a highly diastereoselective conjugate addition of enantiopure secondary lithium amides to a,b-unsaturated esters to facilitate an efficient synthesis of (R)-sitagliptin 3. The main challenge in this area is to prepare enantioselectively the stereocenter present in the b-amino acid unit.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…c o m / l o c a t e / t e t a s y Rh-catalyzed asymmetric hydrogenations of an enamine under high pressure; 11 (iii) biocatalytic or Ru-catalyzed reductive aminations of a b-ketoamide. 12 Quite recently, Davies et al 13 reported on a highly diastereoselective conjugate addition of enantiopure secondary lithium amides to a,b-unsaturated esters to facilitate an efficient synthesis of (R)-sitagliptin 3. The main challenge in this area is to prepare enantioselectively the stereocenter present in the b-amino acid unit.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…2 Representatives of this class are wellknown not only as versatile intermediates in organic synthesis and in many other reactions, 3,4 but also as reagents for synthesis of heterocyclic compounds, 5 inhibitors of enzymes, 6 precursors of peptides, 7 amino-acids, 8 which, in turn, exhibit antibiotic, 9 antifungal, 10 and other important biological and pharmacological properties. 11,12 The coordination behaviour of aminonitriles in the complexation reactions with Cu(I) salts can be characterized on the basis of only several related, 13,14 or closely related, 15 compounds, though the matter under discussion is still relevant. It has been noticed that atoms of Cl or Br compete for space in coordination polyhedron with allyl groups and cyano group in the halide complexes of Cu(I) with diallylaminopropanenitrile (the tertiary amine N-atom is protonated).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of synthetic procedures were developed to synthesize Sgli and its precursors [1,[8][9][10][11][12]. Some of these methods carry the possibility of enantiomeric contamination with the undesired (S)-enantiomer of enantiopure Sgli, and therefore enantioselective analytical methods are necessary to control the enantiomeric purity of pharmaceutical Sgli preparations.…”
Section: Introductionmentioning
confidence: 99%